Canon Law as the Universal Law of the Catholic Church and the Proper Laws of Institutes of Consecrated Life - Yohanes Wilson Bei Lena Meo (Forum, 2023)
The course on particular law concerning the specification, complement and adaptation of universal law, has as its objective to show the importance of particular law through the specificity of ecclesial law both in its theological foundations and in its application in various juridical fields. One of the topics discussed in the course is about the relationship between universal and the particular law of the institutes of consecrated life. The aim of this paper is to considered the topic. This article will be divided into sections covering the important principles in relating universal law to the particular law of consecrated life.